ANALISIS OBJEKTIVITAS PENENTUAN KELAYAKAN BANTUAN SOSIAL MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING: STUDI KASUS WILAYAH PEDESAAN INDONESIA - Lanamey Praisy Indiana Rawung; Sondy Campvid Kumajas; Medi Hermanto Tinambunan (LPPM Universitas Abdurrab, 2026)
The determination of eligibility for social assistance recipients at the village level still faces challenges related to subjectivity, inaccurate targeting, and manual data management, which potentially lead to inefficiency and unfairness in decision-making processes. This study aims to design and develop a web-based decision support system to objectively and systematically determine social assistance eligibility in Tandengan Village. The research employs an applied research approach with a descriptive method. Data were collected through observations and interviews with village officials and subsequently analyzed using the Simple Additive Weighting (SAW) method based on three main criteria: income level, number of dependents, and type of occupation. The results indicate that the developed system is capable of managing population data in an integrated manner, performing automatic eligibility calculations, and generating recommendations for social assistance recipients objectively, transparently, and efficiently. The implementation of the SAW method has proven effective in minimizing subjectivity compared to the previously used manual selection process. This study concludes that a SAW-based decision support system is effective for supporting social assistance eligibility determination at the village level. Furthermore, the system provides added value by enhancing transparency in the selection process and offering a traceable calculation record as an audit trail, thereby strengthening accountability and governance in social assistance distribution.